Satire and Sarcasm in Government Fuel Policy Critique: A Pragmatic Analysis of Rian Fahardhi’s TikTok Video - Ramadhani, Resky Suci; Asia, Yunita Aluakafani; Haliq, Abdul (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This study investigates how satire and sarcasm serve as pragmatic devices in a single TikTok video by Rian Fahardhi addressing Indonesia’s subsidized fuel policy. It aims to delineate the distinctive linguistic strategies such as ironic framing, metaphorical exaggeration, and mocking lexical choices through which public discontent is articulated, and to assess their implications for digital political discourse. Employing a qualitative descriptive methodology within a pragmatic framework, the research analyzes the video’s transcript selected via purposive sampling, focusing on illocutionary acts and impoliteness strategies that breach politeness norms to amplify critique. The findings reveal that satire manifests subtly through rhetorical questions and ironic contrasts, while sarcasm appears more explicitly in stark lexical juxtapositions and mocking tonal shifts (e.g., “it feels like we got beaten and given candy”) tic maneuvers not only expose policy inconsistencies but also leverage TikTok’s multimodal affordances to engage and persuade audiences. The study corroborates Culpeper et al.’s model of impoliteness and demonstrates critical humor’s potency as sociopolitical resistance, underscoring TikTok’s emerging role as a platform for nuanced policy critique.